2002
DOI: 10.1080/135562102200120460
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin skin testing in intravenous drug users: differences between HIV‐seropositive and HIV‐seronegative subjects

Abstract: The prevalence of tuberculin skin test reactions among intravenous drug abusers and differences in tuberculin skin test positivity between HIV-seropositive and HIV-seronegative subjects were evaluated in a cross-sectional study of 1131 subjects. They were recruited from a therapeutic community, from those who attended the centre for the treatment of drug addiction and from those who visited for any reason an acute tertiary-care hospital in Vitoria-Gasteiz, Basque Country (Spain). All subjects underwent skin te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…This study corroborates earlier reports that the immunosuppressive effect of HIV infection itself impairs TST reactivity and may contribute to cutaneous anergy and potentially reduces its ability to detect LTBI [36,37]; this may be particularly true since almost half (45.6%) of the HIV-infected prisoners in this sample had a CD4 ≤350 cells/μL. Among PWIDs in the U.S., Graham et al .…”
Section: Discussionsupporting
confidence: 91%
“…This study corroborates earlier reports that the immunosuppressive effect of HIV infection itself impairs TST reactivity and may contribute to cutaneous anergy and potentially reduces its ability to detect LTBI [36,37]; this may be particularly true since almost half (45.6%) of the HIV-infected prisoners in this sample had a CD4 ≤350 cells/μL. Among PWIDs in the U.S., Graham et al .…”
Section: Discussionsupporting
confidence: 91%
“…The possible reason for these discrepancies can be explained by the differences between CD4+ counts in HIV infected patients which results different immunoresponse to PPD test. As Portu et al (19) indicated that in HIV positive group there was a significant association between results of PPD test and CD4+ T-lymphocyte count. The rate of positive PPD test was similar in HIV seropositive and seronegative cases when the CD4+ count was equal or greater than 500 cells/mm3.…”
Section: Discussionmentioning
confidence: 91%
“…Somewhat paradoxically, HIV prevalence was lower among PWID who were QFT-positive, but others have reported similar findings. 17,24 Other studies used TST, which is known to have reduced sensitivity among individuals with HIV due to immunosuppression. The current study used QFT, which has greater sensitivity than TST among individuals with HIV and produces indeterminate—rather than negative—results if the subject is severely immunosuppressed.…”
Section: Discussionmentioning
confidence: 99%